HCnN anions in the ISM: exploring their existence and new paths to anionic carbonitriles for n = 3, 5. Issue 21 (21st May 2019) - Jerosimić, Stanka V.; Wester, Roland; Gianturco, Franco A.
Abstract : We have selected two neutral C-rich linear molecules, HC3 N and HC5 N, which are very abundant in the interstellar medium (ISM) to computationally investigate the stability of their anions and their possible existence in outer space, for which thus far there is no available evidence. Abstract : We have selected two neutral C-rich linear molecules, HC3 N and HC5 N, which are very abundant in the interstellar medium (ISM) to computationally investigate the stability of their anions and their possible existence in outer space, for which thus far there is no available evidence. Our present, ab initio structural studies strongly indicate that the neutral cyanopolyynes can have two types of stable anions by either forming slightly distorted non-linear structures of anionic Valence Bound States (VBSs), or linear more weakly bound dipole-bound states (DBSs) produced directly from the initial neutral linear configurations. Our present calculations further show that the stability of these anions increases with the number of C atoms in the chains. We carefully analyze possible physical causes for their lack of observation thus far: from the increased complexity of their rotational spectra with respect to those already observed, to their possible losses due to them entering the formation network of the C3 N − and C5 N − carbonitrile anions, which have been observed in the circumstellar envelopes and in the Titan atmosphere. We specifically suggest that de-hydrogenation reactions of the initial anions could take place by following either of two possible, well-known mechanisms: the fragmentation path usually ascribed to Dissociative Electron Attachment (DEA) processes or chemical recombination active in exothermic reactions with the H, N and O atoms present in the circumstellar envelopes. The results from such processes would be the loss of the stable anions of cyanopolyynes and the additional formation of their anionic carbonitriles.